Hospitalised COVID-19 outcomes are predicted by hypoxaemia and pneumonia phenotype irrespective of the timing of their emergence - Jennifer LY Tsang; Laura Spatafora; Andrew P Costa; MyLinh Duong; Aaron Jones; Mats Junek; Terence Ho; Rebecca Kruisselbrink; Tyler Pitre; Brittany Salter; Bianca DeBenedictis; Jessica Kapralik; et al. (BMJ Open, 2022)
Objective Describe the prevalence and clinical course of patients hospitalised with COVID-19 based on oxygenation and pneumonia status at presentation and determine the incidence of emergent hypoxaemia or radiographic pneumonia during admission.Methods A retrospective study was conducted using a Canadian regional registry. Patients were stratified according to hypoxaemia/pneumonia phenotype and prevalence. Clinical parameters were compared between phenotypes using χ2 and one-way Analysis of variance (ANOVA). Cox analysis estimated adjusted Hazard Ratios (HR) for associations between disease outcomes and phenotypes.Results At emergency department (ED) admission, the prevalence of pneumonia and hypoxaemia was 43% and 50%, respectively, and when stratified to phenotypes: 28.2% hypoxaemia+/pneumonia+, 22.2% hypoxaemia+/pneumonia−, 14.5% hypoxaemia−/pneumonia+ and 35.1% hypoxaemia−/pneumonia−. Mortality was 31.1% in the hypoxaemia+/pneumonia− group and 26.3% in the hypoxaemia+/pneumonia+ group. Hypoxaemia with pneumonia and without pneumonia predicted higher probability of death. Hypoxaemia either <24 hours or ≥24 hours after hospitalisation predicted higher mortality and need for home oxygen compared with those without hypoxaemia. Patients with early hypoxaemia had higher probability of Intensive care unit (ICU) admission compared with those with late hypoxaemia.Conclusion Mortality in COVID-19 infection is predicted by hypoxaemia with or without pneumonia and was greatest in patients who initially presented with hypoxaemia. The emergence of hypoxaemia was predicted by radiographic pneumonia. Patients with early and emergent hypoxaemia had similar mortality but were less likely to be admitted to ICU. There may be delayed identification of hypoxaemia, which prevents timely escalation of care.